On the New US Military Strategy in the Arctic - Valeriy N. Konyshev; Alexander A. Sergunin (Арктика и Север)
The article discusses the new US military strategy in the Arctic, announced by the administration of J. Biden in July 2024. It replaced a similar document issued under D. Trump in 2019. The authors raise the question of what has changed in the approaches to Arctic security, given the sharp nature of the contradictions between Republicans and Democrats. The article demonstrates that, in general, the US Arctic military policy has maintained continuity; the only difference is the attempt of the Democrat administration to formulate more specific areas of activity to protect US security interests. In the text of the strategy, when assessing threats, China, not Russia, is placed in the first place in terms of importance. At the same time, the formulation of threats to US security in the region is too general and seems far-fetched. The main areas of implementation of the current US military strategy include measures to develop communication, command, control and intelligence systems; to improve military infrastructure; to strengthen the US and NATO military presence in the Nordic countries and to develop defense cooperation. In general, the strategy is confrontational in nature, especially since the US, having obtained geopolitical benefits after Finland and Sweden joined NATO, clearly intends to use them to gain unilateral advantages. However, there are limiting conditions that will prevent the US from fully realizing the plans of this strategy. The main threat to Russia’s security in the region is the constant military presence and build-up of US/NATO military infrastructure in close proximity to its Arctic borders, as well as Washington’s intention to implement the principle of “freedom of navigation” in the Arctic Ocean, including the Northern Sea Route.